1992
DOI: 10.1056/nejm199202203260801
|View full text |Cite
|
Sign up to set email alerts
|

The Use of β-Agonists and the Risk of Death and near Death from Asthma

Abstract: An increased risk of death or near death from asthma was associated with the regular use of inhaled beta 2-agonist bronchodilators, especially fenoterol. Regardless of whether beta-agonists are directly responsible for these adverse effects or are simply a marker for more severe asthma, heavy use of these agents should alert clinicians that it is necessary to reevaluate the patient's condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
310
0
16

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,140 publications
(340 citation statements)
references
References 16 publications
14
310
0
16
Order By: Relevance
“…These results are in agreement with clinical studies that have demonstrated that S-salbutamol can induce airway hyperresponsiveness in patients with asthma. It has been suggested that these paradoxical responses may be reduced by removing the dose of S-enantiomers [5,11]. Besides, Rsalbutamol is now commonly available for the treatment of obstructive lung disease and further R-isomers preparations of β 2 -agonist are under development in man (3) Like human obstructive bronchial diseases, equine obstructive pulmonary disease, also known as heaves or recurrent airway obstruction (RAO), is a common equine chronic pulmonary disease, in which the prominent symptom is airway obstruction which is treated with β 2 agonists [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with clinical studies that have demonstrated that S-salbutamol can induce airway hyperresponsiveness in patients with asthma. It has been suggested that these paradoxical responses may be reduced by removing the dose of S-enantiomers [5,11]. Besides, Rsalbutamol is now commonly available for the treatment of obstructive lung disease and further R-isomers preparations of β 2 -agonist are under development in man (3) Like human obstructive bronchial diseases, equine obstructive pulmonary disease, also known as heaves or recurrent airway obstruction (RAO), is a common equine chronic pulmonary disease, in which the prominent symptom is airway obstruction which is treated with β 2 agonists [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have documented that S-salbutamol can potentiate the effects of spasmogens in airway smooth muscle from both guinea-pigs and humans , with a number of clinical studies also reporting worsening of airways hyperresponsiveness in animals [3] and in subjects with asthma [4]. It has also been documented that the metabolic clearance of S-salbutamol occurs much less rapidly than Rsalbutamol [5], and thus the paradoxical responses may persist after the beneficial effects of (R)-salbutamol have waned [2], particularly after chronic use of the drug. S-salbutamol has also been reported to have proinflammatory effects that could negatively affect the airways [6].…”
Section: Introductionmentioning
confidence: 99%
“…Population studies identify increased risk from continuous scheduled use of β2-receptor agonists but don't identify those individuals most at risk. 3,4 The studies of β2-adrenoreceptor polymorphisms reviewed by Binaei et. al.…”
Section: See Related Article Page 22mentioning
confidence: 99%
“…2 These practices have shifted dramatically, and the most recent data show that although asthma prevalence continues to increase, the death rate has decreased.…”
mentioning
confidence: 99%